DEVELOPMENT OF WEBSITE-BASED LEARNING MEDIA ON BASIC COMPETENCIES OF TUBER PROCESSING - Firda Fadilah; Sri Handayani; Dewi Nur Azizah (Journal of Development and Integrated Engineering, 2022)
Learning that takes place online during a pandemic makes the learning process more challenging because of the difficulty of conditioning the learning process. The role of learning media is important to make learning more interesting which is expected to improve student learning outcomes. This study aims to determine the feasibility of website-based learning media on the basic competence of tubers processing. The development of this website-based learning media uses the ADDIE method which consists of five stages, namely: (1) Analysis; (2) Design (Design); (3) Development (Development); (4) Implementation, and (5) Evaluation. Keywords: ADDIE, learning media, website.